Empowering Futures: The Role of Job Satisfaction Among Marginalized Female Workers in Supporting Children's Education and Community Participation - Iskandar Agung; Imran Siregar; Herlinawati Herlinawati; Abdul Kadir Ahmad; M. Calvin Capnary (STAI Hubbulwathan Duri, 2024)
This study explores the impact of job satisfaction among female garment workers on their children’s educational continuity, focusing on the role of community involvement in supporting education. A qualitative approach was employed, utilizing focus group discussions, interviews, and document analysis to gather data. Thematic analysis was conducted to identify patterns and derive conclusions. Findings reveal that while female garment workers express job satisfaction due to the income it provides for family needs and education costs, barriers persist in advancing their children's education. Economic constraints, cultural norms prioritizing boys’ education, and limited access to resources inhibit aspirations for secondary and higher education. Additionally, the extensive work hours of mothers reduce their engagement in children's education. Community participation is minimal, affected by cultural attitudes, economic limitations, and ineffective policy implementation. This results in inadequate support for educational infrastructure, such as study rooms, libraries, and sports facilities. The interplay between job satisfaction and systemic barriers illustrates a paradox where income supports basic educational needs but fails to foster long-term educational aspirations. The lack of collective community action exacerbates the situation. To address these challenges, collaboration among companies, governments, and communities is essential. Initiatives such as targeted CSR funding, scholarships, and the development of educational infrastructure can mitigate barriers and improve educational outcomes for children of female garment workers.